2008
DOI: 10.1007/s11095-008-9677-1
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Aqueous Solubility and Dose on the Pharmacokinetic Profiles of Resveratrol

Abstract: Aqueous solubility barrier might affect the speed but not the extent of resveratrol absorption. Further, dose manipulation (up to 50 mg kg(-1)) did not have a significant impact on the oral bioavailability of resveratrol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
125
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 184 publications
(134 citation statements)
references
References 26 publications
6
125
1
Order By: Relevance
“…30 Our RL-FNPs showed curves of liberation with an initial burst, reaching resveratrol saturation of the aqueous medium in 3-4 hours and maintaining a resveratrol concentration higher than 15 mg/L in PBS medium over a period of 80 hours. Considering a volume of 25 mL of PBS, 0.5 mg of resveratrol was released initially until medium saturation was reached.…”
Section: Release Of Resveratrol From Rl-fnpsmentioning
confidence: 73%
“…30 Our RL-FNPs showed curves of liberation with an initial burst, reaching resveratrol saturation of the aqueous medium in 3-4 hours and maintaining a resveratrol concentration higher than 15 mg/L in PBS medium over a period of 80 hours. Considering a volume of 25 mL of PBS, 0.5 mg of resveratrol was released initially until medium saturation was reached.…”
Section: Release Of Resveratrol From Rl-fnpsmentioning
confidence: 73%
“…Due to its different physicochemical properties such as molecular weight, number of hydrogen bond donor and acceptor, rotatable bond, clogP, and polar surface area, resveratrol has poor biomembrane permeability. The poor oral bioavailability [14] considerably less than 1% would attribute to different the metabolic issue [44], such as very short half-life in rat liver microsomes. Furthermore, poor oral bioavailability is due to the first-pass metabolism in intestine [45,46], while increased dose and repeated dose escalation would not affect the bioavailibity.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that pre-clinical studies using the same resveratrol concentration as ours have previously demonstrated mood lifting effects, not just following intraperitoneal administration (acute or chronic regimen, respectively; Samardzic et al, 2013;Wang et al, 2013), but also after intra-gastric administration (acute or chronic regimen, respectively; Xu et al, 2010;Yu et al, 2012), thereby alleviating some of the concerns surrounding first-pass effects. In contrast to these studies, we used both (ethanol and 2-Hydroxypropyl)-b-cyclodextrin to increase the aqueous solubility and stability of resveratrol, an approach that, while not likely to be effective at enhancing the extent of the oral bioavailability, can nonetheless enhance its rate (Amri et al, 2012;Das et al, 2008). Future investigations may address issues of optimization of oral bioavailability by considering alternative formulations (Amri et al, 2012), the use of resveratrol derivatives with higher oral availability, such as pterostilbene (e.g.…”
Section: Discussionmentioning
confidence: 99%